2004
DOI: 10.1002/ajmg.a.30185
|View full text |Cite
|
Sign up to set email alerts
|

A patient with a de novo 15q24q26.1 interstitial deletion, developmental delay, mild dysmorphism, and very blue irises

Abstract: We report on a patient with a de novo 15q24q26.1 interstitial deletion. She presented with developmental delay, behavioral characteristics, and mild dysmorphism with very blue irises. We review the limited literature of interstitial 15q deletions. There was no distinct phenotypic overlap between these two cases in literature and the present patient. Additional reports are necessary in order to establish a possible recognizable deletion 15q24q26.1 phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Nine cases with deletions involving chromosome 15q22‐q24 (Fig. 4 and Table I) have been reported in the literature [Clark, 1984; Yip et al, 1986; Formiga et al, 1988; Martin et al, 1990; Bettelheim et al, 1998; Smith et al, 2000, Spruit et al, 2004]. However, only one of these patients has a cryptic deletion, similar to Patients 1 and 2 in the present report.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Nine cases with deletions involving chromosome 15q22‐q24 (Fig. 4 and Table I) have been reported in the literature [Clark, 1984; Yip et al, 1986; Formiga et al, 1988; Martin et al, 1990; Bettelheim et al, 1998; Smith et al, 2000, Spruit et al, 2004]. However, only one of these patients has a cryptic deletion, similar to Patients 1 and 2 in the present report.…”
Section: Discussionsupporting
confidence: 86%
“…g : del(15)(q21q24) [Formiga et al, 1988]. h : del(15)(q24q26.1) [Spruit et al, 2004]. i : del(15)(q24 → qter) [Bettelheim et al, 1998].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…With the exception of the common recurrent 15q11.2q12 deletions which, depending on parental origin, result in either Prader–Willi syndrome or Angelman syndrome, and deletions and duplications in 15q13.3 (Sharp et al 2008; Ben-Shachar et al 2009), rearrangements of chromosome 15q are relatively rare (Cushman et al 2005); those involving the 15q24 region were described in patients with growth deficiency, psychomotor retardation, and birth defects (Bettelheim et al 1998; Clark 1984; Formiga et al 1988; Spruijt et al 2004). Cushman et al (2005) reported three patients with a 15q24 deletion and reviewed the previously reported cases with cytogenetically visible deletions involving the 15q22q24 region.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, interstitial deletion of 15q26 appears to be rare. There have been a few 15q interstitial deletion cases reported, and the majority of them are cytogenetically visible deletions of various sizes in the 15q21.1-26.1 region [Martin et al, 1990;Spruijt et al, 2004]. We present a child with developmental delay, mild dysmorphic features and an apparently balanced translocation t(15;22)(q26.1;q11.2).…”
Section: Introductionmentioning
confidence: 91%